A New Eu3+‐Labeled Method for Anticardiolipin Antibody IgM. Issue 4 (22nd March 2014) - Ye, Yan; Hu, Zhigang; Liu, Jie; Chen, Guoqian; Zhou, Yaohong
<x xml:space="preserve">Abstract</x> Background The anticardiolipin antibodies (aCL) test has become a laboratory standard for the clinical diagnosis of antiphospholipid syndrome (APS). To better the quantitative detection of aCL‐IgM so as to classify patients correctly and timely as APS positive, we established herein a new immunoassay based on a time‐resolved fluoroimmunoassay (TRFIA). Methods The complex of cardiolipin plus bovine anti‐β2 glycoprotein‐I was used as antigen fixed on microtiter plates to detect serum aCL‐IgM, and Eu3+‐labeled rabbit antihuman IgM was used as conjugate. The precision, sensitivity, specificity, coefficient of recovery, and stability of the assay were evaluated, and comparison with the traditional, classical enzyme‐linked immunosorbent assay (ELISA) was also made. Results The detection limit of the aCL‐IgM TRFIA kit we established was 0.1 MPL U/ml, with a wider detectable range than commercial ELISA ones when a strong‐positive specimen was diluted from 2, 630.9 to 0.08 MPL U/ml. There was a good liner range within 0.16 to 2, 630.9 MPL U/ml, whereas it was within 5.14 to 328.86 MPL U/ml when using three commercial ELISA ones. The average intra‐ and interassay variability was 3.19 and 3.70%, respectively. The mean recovery rate was 101.95%. The clinical diagnostic specificity was 98%. Additionally, the established assay kit presented good characteristics of stability and correlated well with the ELISA, and the correlation coefficient was 0.955. Conclusion The aCL‐IgM TRFIA provides an approach to a more sensitive and reliable diagnosis of APS. Further validation of its use is required.